Implementation Religious Character Values for Students Through School Extracurricular Programs - Rayhan Feyza Alfarikh; Fensy Anandre Saleh; Sri Hartati; Marjoko Susilo; Epi Puspita; Yeti Hartini; Hesty Ramadhani (International Journal of Multidisciplinary Research of Higher Education, 2021)
Character is an important thing in the learning process. Positive and moral values must be instilled in students, especially in the era of globalization, many students are negligent about character education. This study aims to determine the inculcation of religious character values in students through the school's extracurricular program. This study uses a qualitative method with a phenomenological approach. Data sources were taken from fifteen informants through in-depth interviews. Informants were obtained from a school principal, four Islamic Religious Education teachers, and ten spiritual members. The results of the analysis show that there are fifteen themes in implementation religious character values in students through the school's extracurricular program. The fifteen themes are i) Islamic Studies, ii) Islamic Seminars, iii) Murajaah the Quran, iv) Kahatam the Quran, v) Ramadhan Islamic Boarding School, vi) Commemoration of Eid al-Fitri and Eid al-Adha, vii) Milad of the Prophet Muhammad SAW, viii) Isra Miraj Commemoration, ix) Faith and Piety Building Night, x) Halal Bi Halal, xi) Rihla, xii) Marawis, xiii) Calligraphy, xiv) Nasyid. The results of this study can be used as initial data for subsequent research in examining problems in different contexts.